Teacher's Perception Regarding the Use and Challenges of ICT in Teaching-learning - Joshi, Bishnu Maya (Ganeshman Darpan, 2023)
ICT is considered a better tool for improving the quality of education. It is an effective network to develop the whole nation through the development of education. This study explored the Use of Information and Communication Technology in teaching-leaning economics classrooms at the university level. The study focused on the Mahendra Ratna Campus of Tribhuvan University. It had two objectives, i.e., to explore the teachers' perception regarding the use of ICT in an economics classroom and to examine the challenges that economics teachers face in using ICT tools in the economics classroom. With a focus on qualitative research, the study used a phenomenological design with five purposively chosen participants from Mahendra Ratna Campus, Tahachal. The researcher's experiences and the experiences of others have to be included in the study's philosophical framework. This inquiry used the Heideggerian phenomenological research design. This study found the keen interest of economics teachers in using ICT in their classrooms. Teachers are considering ICT as a current context needs in education. However, teachers think of ICT as an emerging tool for teaching-learning and have faced many challenges in the classroom to use it.